Why should we still care about the stavudine dose? - Steve Innes; Mark Cotton; Francois Venter (AOSIS, 2011)
Current recommendations advise that stavudine be phased out of use. The logistics and cost of switching are significant, and the World Health Organization has forecast that 1.55 million people will still be on stavudine-based antiretroviral therapy by the end of 2012. Stavudine is co-formulated in many countries, is very cheap and effective, and is well tolerated in initial therapy. However, the 40 mg BD dose was associated with considerable long-term toxicity. Several studies suggest that half the original recommended dose has excellent antiviral efficacy with significantly reduced metabolic side-effects. Despite generic tenofovir now being cheaper than zidovudine, tenofovir consumes the majority of adult antiretroviral programme medication budgets in programmes in Africa, where it is used in first-line therapy. Abacavir is far more expensive than zidovudine or tenofovir, and is a major cost driver in paediatric programmes with access to abacavir-based first-line treatment. Low-dose stavudine may offer the only cheaper (and possibly as effective and safe) alternative to programmes grappling with limited financial resources.